Work-related burnout and its associated factors among midwives working at public hospitals in northwest Ethiopia: a multi-centered study - Mengistie, Berihun Agegn; Azene, Zelalem Nigussie; Haile, Tsion Tadesse; Abiy, Saron Abeje; Abegaz, Marta Yimam; Taye, Eden Bishaw; Alemu, Haymanot Nigatu; Demeke, Muluken; Melese, Mihret; Tsega, Nuhamin Tesfa; Aragaw, Getie Mihret (Frontiers in Psychiatry, 2023)
Introduction Work-related burnout (WRB) is defined as the degree of physical and psychological fatigue and exhaustion that is perceived by the person as related to work. Midwives are vulnerable to work-related burnout due to their physically and emotionally demanding nature of their job. It affects the health of professionals and the quality of care provided. However, there is limited evidence on the burden and predictors associated with work-related burnout among midwives in developing countries, including Ethiopia. This study investigated the burden and contributing factors of work-related burnout among midwives in northwest Ethiopia. Methods A facility-based cross-sectional study was conducted from February 7 to April 30, 2022. A simple random sampling method was used to enroll 640 study participants. The Copenhagen burnout inventory tool was used to assess the magnitude of work-related burnout. A self-administered questionnaire was used to collect data, which was then entered into Epi Data 4.6 software and exported to SPSS version 25 for analysis. A multivariable logistic regression analysis model was fitted to identify factors associated with work-related burnout. The Adjusted Odds Ratio (AOR) with 95% confidence interval (CI) was reported to declare the factors that are significantly associated with work-related burnout. Results The prevalence of work-related burnout was found to be 60.47% (95% CI = 56.6–64.2). Workplace violence (AOR = 3.33, CI: 2.02, 5.48), working hours over 60 h a week (AOR = 4.55, CI: 2.78, 7.43), emotional demand of the job (AOR = 8.85, 95% CI: 4.48, 17.47), exposure to blood and body fluids/sharp injuries (AOR = 5.13, CI: 3.12, 7.13), good superior support (AOR = 0.38, CI: 0.23, 0.63), Job rotation of ≤6 months (AOR = 2.30, CI: 1.28, 4.14) and being stressed (AOR = 2.64, CI: 1.63, 4.26) were all found to be strongly linked to work-related burnout. Conclusion and recommendation This study found a significant level of work-related burnout among midwives working in public hospitals. Experiencing workplace violence, a job rotation of less than or equals to six months, working hours over 60 h a week, good superior support, exposure to blood and body fluids or needle stick injuries and experiencing stress were significant factors that influenced work-related burnout. Therefore, reducing prolonged working hours, promoting supportive management, creating a safe working environment, and applying effective stress prevention strategies are some of the interventions to prevent or alleviate work-related burnout.